Does platelet mass influence the effectiveness of ibuprofen treatment for patent ductus arteriosus in preterm infants?. (1st December 2016) - Akar, Selahattin; Karadag, Nilgun; Gokmen Yildirim, Tulin; Toptan, Handan Hakyemez; Dincer, Emre; Tuten, Abdulhamit; Yavuz, Taner; Topcuoglu, Sevilay; Karatepe, Hande Ozgun; Ozalkaya, Elif; Karatekin, Guner; Ovali, Fahri
Abstract: Objective : The aim of this study is to evaluate whether the platelet mass in the first 24 h of life is effective on closure of patent ductus arteriosus (PDA) or not. Study design : Preterm infants with a gestational age of < 32 weeks, hospitalized at a tertiary neonatal intensive care unit (NICU) and requiring medical treatment (intravenous or oral ibuprofen) for hemodinamically significant PDA (hsPDA) were enrolled in this study. The patients were divided into two groups after first course of pharmacologic treatment according to closure of PDA (Group 1: PDA closure, Group 2: PDA without closure). Groups were compared in terms of demographics findings, morbidities, platelet measurements like counts, mean platelet volume (MPV) and platelet mass (platelet count × mean platelet volume). Results : The study included 77 preterm newborns in Group 1, and 30 preterms in Group 2. There were no differences in birth weight, gestational age, gender and maternal risk factors between the study groups. The mean platelet count in the first postnatal blood count was in Group 1: 211.3 ± 89.2 × 10 3 /mm 3 and in Group 2: 216.5 ± 26 × 10 3 /mm 3, respectively ( p = 0.783). The mean platelet volumes (MPV) were similar in both groups ( p = 0.535). No statistically significant difference between platelet mass values was detected (Group 1: 1811 ± 884 fl/nl, Group 2: 1868 ± 717 fl/nl) ( p = 0.753). Conclusion : Our data suggest that platelet count, MPV and platelet mass did not affect the closure of hsPDA with ibuprofen.